Plasticity in algal stoichiometry: Experimental evidence of a temperature‐induced shift in optimal supply N:P ratio. (3rd March 2017) - Thrane, Jan‐Erik; Hessen, Dag O.; Andersen, Tom
Abstract: There is growing empirical and theoretical evidence for a positive relationship between the nitrogen (N)‐to‐phosphorus (P) ratio of phytoplankton and temperature. However, few have tested how the optimal supply N:P ratio; the dissolved N:P ratio at which nutrient limitation switches from one element to the other, responds to temperature. In this study, we conducted a factorial experiment crossing 12 temperature levels with 8 supply N:P ratios to determine the effect of temperature acclimation on the optimal supply N:P ratio of the microalgae Chlamydomonas reinhardtii . We found that the optimal supply N:P increased in a sigmoidal manner from 26.5 to 36.5 (atomic ratio) over a temperature gradient spanning from ∼10 to 18°C, with the steepest change around 15°C. This result is in accordance with trends observed for cellular and seston N:P ratios, and indicates that phytoplankton populations may be shifted toward N‐limitation in a scenario of warmer waters.